Mobile health intervention for youth with sickle cell disease: Impact on adherence, disease knowledge, and quality of life. Issue 8 (25th April 2018) - Anderson, Lindsay M.; Leonard, Sarah; Jonassaint, Jude; Lunyera, Joseph; Bonner, Melanie; Shah, Nirmish
Abstract: Background: Adherence to illness self‐management among youth with sickle cell disease (SCD) positively impacts health outcomes and decreases overall healthcare costs. Despite this, children with SCD face several barriers to adherence, with adherence rates that remain moderate to low. The current feasibility study examined the Intensive Training Program (ITP), a mobile health (mHealth) intervention for youth with SCD designed to promote disease knowledge, adherence, and patient‐provider communication. Procedure: Youth with SCD prescribed hydroxyurea between ages 7–18 completed baseline disease knowledge and psychosocial assessments and then were provided with the ITP app. Youth participated in the 90‐day ITP, during which they completed three education modules, tracked adherence through daily self‐recorded videos on the app, and received video messages from providers. Participants completed poststudy knowledge, psychosocial, and feasibility questionnaires. Medication possession ratio (MPR) was obtained via pharmacy‐refill rates. Results: Thirty‐two youths (mean age = 13.0 years) participated, with an average adherence tracking rate of 0.6 (standard deviation   = 0.34). All participants demonstrated increased MPR (0.57–0.74, P  < 0.001, d   = 0.75) and disease knowledge (59.6–88.6%, P  < 0.001). There was variable engagement in the ITP; completers demonstrated significantly better SCD‐related functioning ( P  < 0.05), higher parent‐reported treatment functioning ( P  < 0.05), and lower pain impact than noncompleters of the ITP ( P  < 0.05). Conclusions: Results support the ITP can feasibly be implemented to promote adherence among youth with SCD. All participants demonstrated increased adherence and disease knowledge. However, there was variable engagement and only intervention completers showed improvements in psychosocial outcomes. Further research is needed to evaluate long‐term outcomes and ways to promote engagement in mHealth interventions among the youth.